Evaluation Report on District Poverty Initiatives Project (DPIP)In Madhya Pradesh - Planning Commission (Planning Commission, 2005)
The District Poverty Initiatives Project (DPIP), being implemented in the State of Madhya Pradesh, is designed to alleviate rural poverty through empowerment of the disadvantaged groups, especially women. It was launched in March 2001 in 2,932 villages spread over 53 blocks of 14 districts and is scheduled to be completed in June 2006. At the instance of the Government of Madhya Pradesh, the Programme Evaluation Organization (PEO) of the Planning Commission undertook the evaluation of DPIP to assess: efficacy of the institutional structure and implementation mechanism; physical and financial performance; sustainability and replicability of the sub-projects; and impact on the target group. To test the relevant hypotheses and examine various issues, the PEO relied primarily on the data generated through a sample survey of 24 sample villages, 96 common interest groups (CIGs), 192 beneficiaries, 8 Control villages, 16 households from the Control Villages spread over four districts of the state. The secondary data were collected from the records of implementing department of the State Government, sample districts and PFTs. In addition, qualitative information at all levels has also been collected and analyzed.
PEO Report No.192